Pengaruh Strategi Promosi Harga Bundling Terhadap Keputusan Pembelian di Platform E-Commerce: Tiktokshop - Dzakiya Rahmanita; Rabhi Fathan Muhammad (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The bundling price promotion strategy has become a trend in the marketing world, especially in the era of increasingly developing e-commerce. This study aims to analyze the influence of the bundling price promotion strategy on consumer purchasing decisions on the TikTok e-commerce platform. A quantitative approach with a survey method was used in this study, involving respondents who had purchased products with bundled price promotions on TikTok. Data were collected through an online questionnaire and analyzed using multiple linear regression analysis. The results showed that the bundling price promotion strategy had a positive and significant effect on consumer purchasing decisions on TikTok. Consumers reacted positively to the bundling price promotion because they perceived they received higher added value and more affordable prices compared to purchasing products individually. This study provides confirmation in validating related theories and strengthens the findings of previous research. Practically, the results of this study provide empirical evidence for TikTok and other e-commerce platforms that the bundling price promotion strategy can be an effective marketing tool to increase consumer purchasing decisions.